Psychological Changes of Teachers in the Implementation of Semi-Online Learning in Elementary Schools during the Covid-19 Pandemic - Arnika Dwi Asti; Sarwono Sarwono (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The Coronavirus or Covid-19 which appeared in December 2019 is a new type of virus that attacks the respiratory system. The increasing cases of COVID-19 have affected many aspects of life including education with the shifting from offline to online learning. Indeed, this condition changes the psychological condition of the teachers at elementary schools in the Gombong Sub-district.To identify psychological changes of teachers in the implementation of semi-online learning in elementary school children during the Covid-19 pandemic in elementary schools in the Gombong Sub-district. This study is descriptive and quantitative with a cross-sectional design. It involved a sample of 154 people selected using a proportionate stratified random sampling technique. Data were collected in October 2021 using the DASS 42 questionnaire with a validity and reliability value of 0.91. The results of this study showed that most teachers in elementary schools in the Gombong Sub-district were female with a total of 97 people (63.0%). Then, a total of 112 people (72.7%) aged 18-40 years old and 75 people (48.7%) had an income of less than 1 million. Regarding marital status, 132 people (85.7%) were married. Then, 89 people (57.8%) had worked for more than 5 years and 154 people (100%) used semi-online learning. Most of the teachers experienced psychological changes in the form of mild anxiety levels, mild stress levels, and normal depression levels with 76 people (49.4%), 81 people (52.6%), and 144 people (93.5%) respectively. This study reveals that most of the teachers in elementary schools in the Gombong Sub-district experience psychological changes in anxiety and stress, not depression. Abstrak: Adanya fenomena Coronavirus atau lebih dikenal dengan Covid-19 pada awal bulan Desember 2019, yang merupakan jenis virus baru yang menginfeksi sistem respirasi, dan masih terus meningkatnya kasus sampai saat ini sehingga berdampak pada aspek pendidikan yaitu diadakannya pembelajaran daring yang mengakibatkan perubahan psikologis pada guru. Untuk mengetahui perubahan psikologis guru terhadap pembelajaran daring anak sekolah dasar selama pandemi Covid-19 di SD se-Kecamatan Gombong. Metode dari penelitian ini adalah kuantitatif deskriptif dengan pendekatan cross sectional dengan sampel 154 orang yang diambil menggunakan teknik proportionate stratified random sampling. Pengumpulan data dilakukan pada bulan Oktober 2021, instrumen dengan menggunakan kuesioner DASS 42 yang mempunyai tingkatan validitas dan nilai reliabilitas sebesar 0,91. Hasil dari penelitian ini didapatkan bahwa guru di SD se-Kecamatan Gombong mayoritas berjenis kelamin perempuan 97 orang (63,0%), usia 18-40 112 orang (72,7%), penghasilan kurang dari 1 juta 75 orang (48,7%), status perkawinan menikah 132 orang (85,7%), masa kerja lebih dari 5 tahun 89 orang (57,8%), dengan jenis pembelajaran semi daring 154 orang (100%). Sebagian besar guru mengalami perubahan psikologis berupa kecemasan tingkat ringan 76 orang (49,4%), stres tingkat ringan 81 orang (52,6%), dan depresi pada tingkat normal 144 orang (93,5%). Pada penelitian ini didapatkan hasil bahwa sebagian besar guru di SD se-Kecamatan Gombong mengalami perubahan psikologis berupa kecemasan dan stres, serta tidak mengalami depresi.